National Archives of Fiji a systems analysis - Ravatu, Semiti Gaunavinaka 1959-
1. Internal analysis which covered 15 staff members. Their analysis with procedures, objectives of tasks, workflows, attitudes, skills, education, etc. together with observations and interviews during the course of work. A set of structured questionnaires were also used to measure their opinions on the evaluation.